Conditional Survival as a Selection Strategy To Identify Plant-Inducible Genes of Pseudomonas syringae - Marco, Maria L. (American Society for Microbiology, 2003)
A novel strategy termed habitat-inducible rescue of survival (HIRS) was developed to identify genes of Pseudomonas syringae that are induced during growth on bean leaves. This strategy is based on the complementation of metXW, two cotranscribed genes that are necessary for methionine biosynthesis and required for survival of P. syringae on bean leaves exposed to conditions of low humidity. We constructed a promoter trap vector, pTrap, containing a promoterless version of the wild-type P. syringae metXW genes. Only with an active promoter fused to metXW on pTrap did this plasmid restore methionine prototrophy to the P. syringae metXW mutant B7MX89 and survival of this strain on bean leaves. To test this method, a partial library of P. syringae genomic DNA was constructed in pTrap and a total of 1,400 B7MX89 pTrap clones were subjected to HIRS selection on bean leaves. This resulted in the enrichment of five clones, each with a unique RsaI restriction pattern of their DNA insert. Sequence analysis of these clones revealed those P. syringae genes for which putative plant-inducible activity could be assigned. Promoter activity experiments with a gfp reporter gene revealed that these plant-inducible gene promoters had very low levels of expression in minimal medium. Based on green fluorescent protein fluorescence levels, it appears that many P. syringae genes have relatively low expression levels and that the metXW HIRS strategy is a sensitive method to detect weakly expressed P. syringae genes that are active on plants. Furthermore, we found that protected sites on the leaf surface provided a higher level of enrichment for P. syringae expressing metXW than exposed sites. Thus, the metXW HIRS strategy should lead to the identification of P. syringae genes that are expressed primarily in these areas on the leaf.